Construction of knock-out mutants of Escherichia coli BW25113 for improved polyhydroxyalkanoate production - Mohamed Biran, Nurhajirah (2017)
Polyhydroxyalkanoates (PHAs) is linear polyester produced through fermentation of sugar or lipid. Biosynthesis of PHA involves three enzymes which are acetyl-CoA acetyltransferase, acetoacetyl-CoA reductase and PHA synthase. Under growth conditions, PHA is synthesized when excess carbon sources and essential nutrients are limited. Comamonas sp. is one of the strains commonly used for PHA production. However, the strain consist of PHA depolymerase gene in its genome which will influence PHA production. Thus, E. coli was used as a host for PHA production since its genome is well characterized and no depolymerase gene was reported. In this work, PHA biosynthesis operon of Comamonas sp. EB172 was introduced into Escherichia coli BW25113 through pGEM’-T vector. The strain was used for further modification to enhance PHA production thorough metabolic engineering approach. Metabolic engineering through one-step single deletion approach was carried out to identify specific gene related to PHA metabolism in E. coli. Seven genes pgi, frdC, fdnG, focA gltA, pta, and poxB were found to be associated with PHA metabolism. In addition, P1 transduction was conducted to introduce multiple knock-outs in order to enhance PHA production from E. coli. A deletion of two genes of E. coli BW25113 frdCgltA::kan/pGEM’-phaCABCo has produced 53 wt.% of PHA compared to the control strain E. coli BW25113/pGEM’- phaCABCo which was 46 wt.%, respectively. Finally, a combination of three genes deletion were found to give highest PHA production at 64 wt.% as engineered E. coli BW25113 frdCgltApta::kan/pGEM’-phaCABCo. PHA profiling of was compared with Comamonas sp. EB172 and it showed the engineered strain is about 3-fold higher compared to Comamonas sp. EB172 which is only 23 wt.%. Overall, the results indicate that the genes deletion has enhanced PHA production and the genes of frdC, fdnG, focA and gltA were first to report that improve PHA production in E. coli.